1984
DOI: 10.1128/iai.45.1.1-5.1984
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and extracellular events in luminol-dependent chemiluminescence of polymorphonuclear leukocytes

Abstract: When polymorphonuclear leukocytes (PMNL) and soluble or particulate matter interact, the cells produce chemiluminescence. Luminol-dependent light emission from PMNL is linked to the myeloperoxidase (MPO)-H202 system. Light emission from a cell-free MPO-H202 system was found to be totally inhibited by human serum albumin (HSA), and since HSA is a large molecular protein that does not readily gain access to intracellular sites of PMNL, it could be used to determine the importance of extra-and intracellular event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(76 citation statements)
references
References 24 publications
5
70
0
1
Order By: Relevance
“…The luminol molecule reacts with ROS to form excited aminophthalate anions that decay to the ground state with the release of energy in the form of light, which is measured as chemiluminescence (Briheim et al, 1984;Lundqvist and Dahlgren, 1996). The current study has shown that mouse lymphocytes are capable of generating a reproducible increase in the chemiluminescence signal when stimulated with PMA, PAF or trypsin.…”
Section: Discussionmentioning
confidence: 55%
“…The luminol molecule reacts with ROS to form excited aminophthalate anions that decay to the ground state with the release of energy in the form of light, which is measured as chemiluminescence (Briheim et al, 1984;Lundqvist and Dahlgren, 1996). The current study has shown that mouse lymphocytes are capable of generating a reproducible increase in the chemiluminescence signal when stimulated with PMA, PAF or trypsin.…”
Section: Discussionmentioning
confidence: 55%
“…PMNs and the ROS/RNS released by PMNs are strictly interlinked factors involved in the pathogenesis and progression of human inflammatory airway diseases such as chronic obstructive pulmonary disease (COPD), asthma, airway infections and cystic fibrosis (Levine, 1995;Ichinose et al, 2000), as well as equine RAO, EIPH and IAD; therefore, the aim of this study was to examine whether a preparation of hyaluronic acid interferes with ROS and RNS during the course of equine PMN respiratory bursts, and to establish the lowest concentration at which it still has antioxidant activity by means of luminol-amplified chemiluminescence (LACL). LACL is a method that has been widely used to detect the PMN production of ROS/RNS under various conditions (Briheim et al, 1984;Robinson et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, immune aggregates or complexes present within synovial fluid can activate reactive oxidant production by blood neutrophils in vitro [12][13][14]. It is now appreciated that neutrophils can generate reactive oxidants both intracellularly and extracellularly [15][16][17][18] and clearly these events are likely to have different patho-physiological consequences. Whilst intracellular oxidant production (i.e.…”
Section: Introductionmentioning
confidence: 99%